1998
DOI: 10.1101/gr.8.9.929
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of a Genomic Region Containing the Cdc2L1-2 and MMP21-22 Genes on Human Chromosome 1p36.3 and their Linkage to D1Z2

Abstract: Cdc2L1 and Cdc2L2 span ∼140 kb on human chromosome 1p36.3. The products of the Cdc2L genes encode almost identical protein kinases, the PITSLRE kinases, which have functions that may be relevant to the regulation of transcription/splicing and apoptotic signaling. These genes are deleted/translocated in neuroblastomas with MYCN gene amplification, a subset of malignant melanomas, and in a newly delineated deletion syndrome. Here we report that the p36.3 region of human chromosome 1 consists of two identical gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…8A) that encodes unspliced and five alternatively spliced variant transcripts (13,12,11,10, and 9S) was employed to investigate whether ectopic expression of wild-type (WT) and kinase-dead (DN) forms of CDK11 p110 and cyclins L1␣, L2␣, and L2␤ (those isoforms that interact with CDK11 p110 ) affects alternative splicing activity in HuH7 hepatoma cells. In these experiments, total RNA was extracted from HuH7 cells following transient transfection with the E1A minigene and CDK11 p110 and cyclin L expression vectors.…”
Section: Expression Of Cyclin L1/2 Isoforms Alone or In Combination Wmentioning
confidence: 99%
“…8A) that encodes unspliced and five alternatively spliced variant transcripts (13,12,11,10, and 9S) was employed to investigate whether ectopic expression of wild-type (WT) and kinase-dead (DN) forms of CDK11 p110 and cyclins L1␣, L2␣, and L2␤ (those isoforms that interact with CDK11 p110 ) affects alternative splicing activity in HuH7 hepatoma cells. In these experiments, total RNA was extracted from HuH7 cells following transient transfection with the E1A minigene and CDK11 p110 and cyclin L expression vectors.…”
Section: Expression Of Cyclin L1/2 Isoforms Alone or In Combination Wmentioning
confidence: 99%
“…31 For the CDC2L1 gene, it has been reported that 2 distinct promoters, containing CpG-rich sequences corresponding to a previously isolated CpG genomic sequence characterized by Bird and colleagues, are responsible for the expression of transcripts from CDC2L1 gene. 10 However, our study on the methylation status of melanoma cell lines showed that there was no aberrant methylation of CpG islands in the CDC2L1 promoter and thus the decreased PITSLRE expression in these melanoma cell lines was not caused by hypermethylation of the CpG island.…”
Section: Discussionmentioning
confidence: 64%
“…Two CpG-rich sequences upstream of the gene are responsible for the expression of transcripts from CDC2L1 and CDC2L2. 10 In our previous study, we found that 1 allele of the CDC2L1 gene complex on chromosome 1 was either deleted or translocated in 8 of 14 different melanoma cell lines using fluorescence in situ hybridization 11 and that the alterations in these alleles correlate with differences in sensitivity of melanoma cells to apoptotic stimuli. Decreased expression of PITSLRE proteins from the remaining allele was observed in several cell lines and surgical malignant melanoma specimens.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…One sequence described by Manning et al (2), SgK424, may have been an erroneous prediction in that we can find no firm evidence for its existence, although part of the sequence is identifiable within the current genome build, and a further three proteins were recognized subsequent to the Manning et al (2) publication. Two gene products have now been identified within a duplicated genomic region that gives rise to two proteins, CDC2L1 (P21127) and CDC2L2 (Q9UQ88), that differ by only 15 amino acids (4). The second of these, CDC2L2, was not on the original list.…”
Section: Functionmentioning
confidence: 99%